Structure of local populations and phytocoenotic confinement of Elwendia persica in Turkestan Ridge, Uzbekistan (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Abduraimov OS, Mamatkulova IE, Mahmudov AV. 2023. Structure of local populations and phytocoenotic confinement of Elwendia persica in Turkestan Ridge, Uzbekistan. Biodiversitas 24: 1621-1628. The study of ecological and biological features of cenotic and food plants is not only of important general biological significance, but also serves as a basis for the science-based study of resources and the preservation of species diversity. Elwendia persica (Apiaceae) grows in different regions of Central Asia and has been used regularly for several centuries, especially in traditional cuisines. In particular, local residents in mountainous areas collect this plant and benefit economically. This study aimed to assess the coenopopulation and phytocoenotic confinement of E. persica in Turkestan ridge, Djizakh region, Uzbekistan. The study was carried out between 2018 and 2022 and the ontogenetic structure of four coenopopulations of E. persica was studied. Evaluation of age (? - delta) and efficiency (? - omega) of coenopopulations revealed that the studied populations were classified as young (coenopopulations 1, 3, 4) and transient (coenopopulations 2). Analysis of demographic results shows that the density of individuals in the studied communities ranged 1.4-2.05 ind./m2, whereas the ecological density was 1.64-2.73 ind./m2. The coenopopulations had an index of recreation of 0.52-3.57 and ageing index 0 to 0.13. These indicators show that the coenopopulations are in a normal state. The state of coenopopulations was positively affected by a large amount of annual rainfall on the territory.